Insurgency and Insecurity: Bane of Global Literacy Development - T.A. Adebisi (University of Sofia, 2016)
Year-in, year-out, decades after decades and centuries upon centuries, there has continued to be recurrent calls for eradication of illiteracy globally. The experience over the years has, however, shown that no target fixed for eradication of illiteracy has ever been met. There have always been renewed calls for eradication of illiteracy at the expiration of countless number of failed decades set as targets for Education for All without meeting the target. Parts of the major causes of unrealized and unfulfilled dreams of education for all have been challenges posed by insurgency and insecurity bedeviling the entire world. The outbreak of insurgencies culminating in high level of insecurity has hampered children and adults access to all forms of education be it formal, non-formal, or adult education. Due to insurgencies, school have been physically touched, destroyed, burnt and broken down. The systems of education in many countries globally have been adversely affected. Communities scattered and destabilized, people displaced and killed. This paper therefore premised on the existing literature on insurgency and insecurity issues considers them as bane of global literacy development. The paper explores debilitating effects of insurgency and insecurity on literacy development in Africa in particular and the entire world in general. It highlights instances of insurgency in various dimensions world over, the toll it has on security and education and consequently offers suggestions on the way forward with a view to advancing the course of development that the world so much desires especially in terms of education.